PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN ARTICULATE STORYLINE 3 PADA TEMA 8 SUBTEMA 1 PEMBELAJARAN 2 - Zahra Ananti Mulyana; Surti Kurniasih; Rukmini Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Development of interactive learning media using Articulate Storyline 3 on theme 8 subtheme 1 learning 2. This research aims to develop interactive learning media Articulate Storyline 3 on theme 8 subtheme 1 learning 2 and knowing the feasibility of interactive learning media. The research method used is research and Development using the ADDIE model. A validation test was carried out on media, language, and material experts and implemented in class V, totaling 22 students. The results of the research show that the interactive learning media developed has a very feasible category, with media experts at 88% "very feasible", language experts at 100% "very feasible", and material experts at 96%, student responses getting an average of 94%, and Teacher responses obtained an average of 100% "very appropriate". Based on the research results, it can be concluded that interactive learning media uses Articulate Storyline 3 which has been developed is very suitable for use as learning media in the classroom.